Comparative Analysis of Coffee Farming Practices Introduced by Government and the Private Sectors in Paksong District, Champasak Province, Lao PDR - Phommasoulin, Vanthieng; Baconguis, Rowena T.; Dizon, Josefina T.; Jamias, Serlie B. (Silliman Journal, 2022)
This study examined the differences between the governmentsupported farmers (GSF) and the private-led farmers (PLF) in Paksong District, Champasak Province, Lao PDR in terms of investigating the support system available to them and adoption of recommended coffee farming practices. The study is important given the worldwide growth of the coffee industry and the resurgence of interest in coffee bean production. With the thrust of exploring the potentials of private sector to provide critical extension services, it is imperative to investigate the strengths and limitations of both the government and private sector. While private extension is considered an efficient alternative to government, results showed that there is no distinct difference in terms of the strength of methodology and adoption of practices between GSF and PLF. Group extension, a strategy adopted by both the government and private sector, shows promises of strengthening farmer power in facilitating the provision of needed support in information, credit and marketing. Moreover, given the fact that a large number of farmers do not adopt certain recommended farming practices, training of extension workers and farmer extension workers should be prioritized. Promoting farmer’s groups or training farmer leaders who will serve as extension workers might serve as a useful strategy to spread information and promote recommended practices given the geographical condition of the area. Interventions may be addressed through participatory and group methods where farmers themselves play a central role in the education and regulatory aspect of extension. While extensive educational support is given to farmers, the Lao coffee farmers still have difficulty penetrating the export market due to problems in meeting international quality standards. Complementation between the private and government sector in terms of standard setting and provision of support services is particularly important.